The Algorithmic Hippocratic Oath: How AI is Reshaping the Landscape of Medical Ethics - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare is not merely a technological advancement; it is a profound philosophical shift that is forcing...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care